Association of Maternal Obesity and Pregnancy Outcomes - Timoty Krisna Sukoco; Dini Hidayat; Raden Tina Dewi Judistiani (Althea Medical Journal, 2022)
Background: The prevalence of obesity is increasing globally, causing various possible disorders and complications. Maternal and perinatal morbidity and mortality might potentially be affected by maternal obesity. This study aimed to evaluate the association between maternal obesity and pregnancy outcomes.Methods: This retrospective cohort study was part of a larger cohort study performed from July 2016 to July 2017 in West Java, including 223 pregnant women with normal fetuses, who were obese or non-obese pre-pregnancy. Underweight women were excluded. Data on pregnancy outcomes consisting of Caesarean section, preeclampsia, premature rupture of membrane (PROM), preterm birth, post-term birth, small for gestational age (SGA), and large for gestational age (LGA) were collected. The association with maternal obesity was analyzed using the Fisher’s Exact Test to determine the association with a 95% confidence interval, and a p-value <0.05 was considered significant.Results: There was an association between maternal obesity and Caesarean section, with an increased risk in obese mothers compared to non-obese mothers (RR 2.398 CI 1.328-4.329). There was no significant association between maternal obesity and preeclampsia, PROM, preterm birth, post-term birth, SGA, and LGA.Conclusion: Maternal obesity is associated with Caesarean section. A more comprehensive approach is essential for obese pregnant women to ensure the health of both the mother and the infant.